2003
DOI: 10.1038/sj.bjp.0705182
|View full text |Cite
|
Sign up to set email alerts
|

A novel immunosuppressive agent FTY720 induced Akt dephosphorylation in leukemia cells

Abstract: 1 Our previous studies revealed that the immunosuppressive agent, FTY720, mainly induces mitochondria-involved apoptosis in some types of cancer cells, since Bcl-2 overexpression prevents the FTY720-induction of apoptotic stimuli. Furthermore, FTY720 induces G0/G1 cell cycle arrest. The present study further examines the correlation between intracellular signaling kinases with FTY720-induced mitochondria-involved apoptosis. 2 Human T cell leukemia Jurkat was exposed to FTY720. Dephosphorylation of Akt occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
150
3
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(162 citation statements)
references
References 40 publications
7
150
3
2
Order By: Relevance
“…There is now a growing body of evidence showing a powerful therapeutic potential of FTY720 in treatment of various types of cancers, [9][10][11][12][13][14][15]18,29,30 although the underlying mechanisms remain to be clarified. The findings described herein demonstrate for the first time that FTY720 is a potent toxic agent towards ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is now a growing body of evidence showing a powerful therapeutic potential of FTY720 in treatment of various types of cancers, [9][10][11][12][13][14][15]18,29,30 although the underlying mechanisms remain to be clarified. The findings described herein demonstrate for the first time that FTY720 is a potent toxic agent towards ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The antitumor activity of FTY720 has been documented in several cancer models, [9][10][11][12][13][14][15] but not yet in ovarian cancer. We (c) OV2008 and iGROV-1 cells were treated for 24 hrs with 5 μM FTY720 or 5 μM cDDP, and then clonogenic survival assay was conducted as described in Methods.…”
Section: Fty720 Induces Cell Death In Human Ovarian Cancer Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…15) The cells incubated with FTY720 demonstrated features characteristic of apoptosis. However, the association between the phosphorylation of FTY720 and its cytotoxicity against cancer cells is not clear.…”
mentioning
confidence: 98%
“…It has been shown that PP2A, a phosphatase with tumor suppressor activity, 58 regulates cell proliferation survival and differentiation 59,60 by inhibiting at post translational levels the function of mitogenic, anti-and/or proapoptotic and differentiation factors, including the BCR/ ABL-activated Akt and S6 kinases. [61][62][63][64] Since in CD34 þ CML blast crisis cells PP2A activity is impaired by increased levels of BCR/ABL oncogenic kinase (Neviani et al, 2005; manuscript submitted), inhibition of PP2A activity may represent another mechanism by which BCR/ABL sustains and enhances the PI-3K/Akt/mTOR/S6K-dependent efficiency of the translation machinery. Figure 1 Effect of BCR/ABL on the translational machinery.…”
Section: Role Of Pp2amentioning
confidence: 99%